Trans People Are Facing Authoritarianism and Eliminationism: Is Critical Scholarship Failing to Respond? - Todd, Jay (ACME, 2026)
We stand at a perilous juncture wherein trans and gender diverse people in the UK and beyond are increasingly subject to authoritarian and eliminationist political forces. Following the UK Supreme Court judgement of April 2025 and amid the continual emergence of political and policy apparatuses that increasingly call for heightened control, surveillance, and restriction of the scope of trans people’s lives, including the UK’s Equality and Human Rights Commission’s Code of Practice, and the ‘Cass’ and ‘Sullivan’ Reviews, in this piece I ask: are critical scholars failing to act with urgency to protect trans people when most needed? I argue that critical scholars should resist the installation of logics that enforce rigid, hygienically-policed sex/gender binaries, question individuals’ selfhoods and autonomy, and undermine ethical standards, recognising in turn the consequences these hold for all marginalised groups and for conducting critical social science research. Moments of solidarity demonstrate the influence that critical scholars can wield to address the emergency nature of this moment, and to ensure that trans people and trans research can be valued and maintained within the academy. Failing to do so risks the loss of trans scholars and trans scholarship, one that critical scholars would carry as their failure and burden.